Studi Inferensi Fuzzy Tsukamoto Untuk Penentuan Faktor Pembebanan Trafo PLN - Thamrin, Fanoeel; Sediyono, Eko; Suhartono, Suhartono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
One  of  the  strategic  components  of  the  power  system  is  the  transformer.  Disruption  of  the  transformer  can  cause  the  transformer  to burning  and the  transformer  performance to decrease.  Therefore,  in this case  maintenance  and  detection of  damage to  the transformerneeds to  be done regularly  so that  the transformer  can  work within the  period of  maximum  usage. But,  the problem  is the  substantial costs  required  to  ask for  an expert  in  transformer  maintenance  and  inspection  on a regular basis.  Based on  these  issues  it  is necessary to develop software with capabilities equal or close to an expert diagnosis of a transformer with high accuracy and speed of maintenance ontransformers  before  irreparable  damage.  Application  of  expert  system  with  fuzzy  inference  Tsukamoto  for  PT.  PLN  transformer maintenance is an expert system used to detect other types  of disturbances in PT PLN distribution transformers so that maintenance can be performed in accordance with the type of damage or disturbance that occurred in the transformer. This application is equipped with transformer  loading  calculation,  an  imbalance  of   load  on  trafo.  Input  variables  used  in  determining  transformer  loading  and  load imbalance on the current transformer is rated at each phase transformer, the voltage of each phase, power factor and the tra nsformer capacity.Keywords : Expert System,  Fuzzy Tsukamoto, Transformers Maintenance